Pengaruh Judi Online Terhadap Kesejahteraan Masyarakat Muslim Perspektif Fiqh Siyasah - Askana Fikriana; Muhammad Irsyad (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Social change is a change that occurs in the community environment, marked by the emergence of a decline in morals and social values in the surrounding environment. One of these activities is the rise of online gambling, this causes people's finances to be disrupted due to an unstable economy, but they fall into online gambling, which requires them to earn money in bad ways. As time goes by, information technology is being misused in the world of gambling, which offers several platforms through sites and applications that are spread across various social media. The aim of this research is to examine the influence of online gambling on the welfare of the Muslim community from the perspective of siyasah fiqh by using the literature study method in processing the required data and information. As found in reviewing several sources and information, there are various opinions expressed about this issue, some scholars are of the opinion that every gambling game that involves betting in the form of money or the like is prohibited, and there are also those who allow games that use thinking and strategy provided that they do not use betting. and not neglect in worshiping Allah SWT. In Islam itself, it has been explained in Surah Al-Baqarah verse 219 and Surah Al-Maidah verses 90-91 which explains about khamr and gambling, and also explains the conditions when the Prophet found the Muhajirin who were the imams of the Maghrib prayer incorrectly in reciting the holy verse Al- Qur'an due to drunkenness. Gambling and similar activities that cause harm are regulated in government law as stated in Article 303 of the Criminal Code which regulates and provides sanctions to perpetrators who are involved in gambling, in order to create a calm and peaceful community life.